Media Figures as Adolescent Role Models: (Dis)Similarities Between Millennials and Generation Z - Stepanovi Ilic, Ivana Zivorad; Blažanin, Barbara; Mojović Zdravković, Kristina (Psihološka istraživanja, 2023)
In the process of identity formation and individuation from parents, media personalities can serve as role models for adolescents. This may be the case even more so for today’s adolescents (i.e., Generation Z), who have been immersed in new media from birth. This study examines how two generations of adolescents differ regarding media figures they identify as role models and the reasons for their admiration. The data were obtained by surveying Millennial (n = 1283) and Generation Z (n = 1358) adolescents a decade apart. Public figures served as role models for every other Millennial compared to three out of four Generation Z adolescents. Both generations admire media celebrities the most, followed by athletes, with all other types of public figures being far less represented. Patterns of admiration reasons are similar in both generations, with celebrities being admired for their cheerfulness, communicativeness, physical appearance, fame, and popularity. The growing influence of new media is evident from the rising number of media figures that Generation Z identifies as role models compared to Millennials and the emergence of micro-celebrities, e.g., YouTubers and influencers. Generation Z adolescents who admire micro-celebrities were found to have professional aspirations in this domain.